P153 Measuring variation in decision making within lung cancer multidisciplinary team (MDT) meetings–a pilot study. (2nd December 2011) - Donaldson, J W; Ellis, M; Rintoul, R; Baldwin, D R
Abstract : Introduction: MDT meetings are now an essential and integral part of lung cancer services but no formal measurement of the variability of decisions made by these teams has been studied. Variation in decision making may be an important factor influencing the UK-wide differences in lung cancer outcomes and survival.1 Aim: The aim of this pilot study was to develop and trial a tool for measuring variation in decision making within MDTs. Method: Seven anonymised clinical cases were provided for discussion with accompanying radiology and histology to 12 MDTs in two regional lung cancer networks. MDTs were asked to provide a comprehensive plan for further investigation (if necessary) and treatment for each case. They were encouraged to specify modality of treatment. Treatment decisions were compared across the participating MDTs and a simple scoring system devised to rate concordance. 10 MDTs provided enough data for analysis. Straight-forward cases were considered by the investigators to have only one clear preferred treatment. Complex cases were less clear cut and selected to pose more of a challenge to MDTs. Nevertheless, each of these cases had a pre-defined preferred treatment option. Results: The three cases rated straight-forward produced good agreement between MDTs, (Abstract P153 table 1 ) for radical vs palliative treatment. More complex cases resulted in less agreement between MDTs. One case (number 5) was excluded from analysis as it was clearly too ambiguous for MDTs to properly assess. Conclusions: We conclude this method to compare decision making by MDTs is a feasible tool. A roll-out is now planned to a further 50 MDTs to document more clearly the variation in decision making UK-wide. Even with this small sample of MDTs for just two Networks, complex cases clearly produce greater variation in the proportion of patients offered radical treatment.